Pengaruh Kualitas Layanan Terhadap Keputusan Siswa Memilih Yayasan Nurul Insan - Krisnaldy; Syukri, Ahmad; Pasaribu, Veta Lidya (Universitas Pamulang, 2023)
This study aims to determine the effect of service quality and promotion on student decisions tochoose Nurul Insan . This research uses descriptive quantitative research methods and retrievesdata by distributing questionnaires to students of Nurul Insan. The sample used was two classesof Vocational School students majoring in marketing, totaling 55 students. Data analysis wasperformed using classical assumption tests and hypothesis testing using multiple linear regressionmethods with SPSS tools.The results of hypothesis testing from this study are as follows: Servicequality has a positive effect on students' decisionsto choose Nurul Insan where the t value>t table(2.404> 2.003) and sig <0.05 (0.008 <0.05) is obtained. Promotion has a positive effect onstudents'decisions to choose Nurul Insan where the value of t count> t table (2.797> 2.003) andSig <0.05 (0.029 <0.05) is obtained. Service quality and promotion together (simultaneously)significantlyinfluence the student's decision to choose Nurul Insan